Oral health-related quality of life in orthodontics: a cross sectional study on adolescents and adults in orthodontic treatment in Kuantan, Pahang - Cheong, Joo Ming; Zubir, Muhammad Ikram; Iskandar, Muhammad Hanis; Mohd Ibrahim, Mohamad Shafiq (Prince of Songkla University, Thailand, 2025)
Objective: This study aimed to assess the impact of the OHIP subscale on OHRQoL and compare the OHRQoL of adolescents and adults. Material and Methods: A total of 160 subjects (60 adolescents and 100 adults) undergoing orthodontic treatment completed the Malaysian Oral Health Impact Profile (S-OHIP(M)) to assess OHRQoL. The instrument consisted of 14 items, grouped into 7 subscales, which were: (i) functional limitation, (ii) physical pain, (iii) psychological discomfort, (iv) physical disability, (v) psychological disability, (vi) social disability, and (vii) handicap. Mann-Whitney U and Kruskal Wallis tests were applied to compare the OHRQoL between both age groups and demographic characteristics. Results: There was a statistically significant difference in median score for quality of life between adolescents 12(9) and adults 16(8). Physical pain had the highest impact on OHRQoL in both groups; whereas, social disability had the least impact for both groups. Conclusion: This study showed that adult groups reported a higher score of impact on OHRQoL compared to adolescent groups. In addition, adolescents and adults reported physical pain as having the highest impact on OHRQoL during orthodontic treatment, with social disability being the least affected factor in OHRQoL.